Exile and Orphanhood. Fathers and Children in Roberto Bolaño's narrative works - Lorenzo Mecozzi (Enthymema, 2015)
The article explores the relationship between fathers and children in Roberto Bolaño's narrative works. To do so, it is shown how that relationship, both in Bolaño's novels and short stories, is intrinsically linked to the theme of the exile. Once the connection between exile and orphanhood is shown, the article tries to offer an insight of the relationship fathers-children in Bolaño's works and to focus on some key characters. Therefore, specific novels and short stories are analyzed in depth: in particular the article examines the characters and the narrative strategies of Los Detectives Salvajes, 2666 and two short stories contained in Putas Asesinas.